2020
DOI: 10.1097/ccm.0000000000004406
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Integrity of Frontoparietal Connectivity in Traumatic and Anoxic Coma

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
3
17
0
1
Order By: Relevance
“…different mechanisms of brain injury 10,29,[63][64][65][66][67][68][69][70] . While most studies have evaluated the prognostic value of DMN connectivity, others evaluated connectivity between the DMN and other networks 10 , evaluated connectivity within other networks 10,65,71 , or evaluated whole brain connectivity (i.e., matrices of connectivity between many regions across many networks) 65,67 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…different mechanisms of brain injury 10,29,[63][64][65][66][67][68][69][70] . While most studies have evaluated the prognostic value of DMN connectivity, others evaluated connectivity between the DMN and other networks 10 , evaluated connectivity within other networks 10,65,71 , or evaluated whole brain connectivity (i.e., matrices of connectivity between many regions across many networks) 65,67 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As with advanced MRI for CMD, there are several factors to consider if clinically pursuing advanced MRI for neuroprognostication, which are summarized in Figure 3. First, clinicians should ensure that the patient population is appropriate, as only certain brain injury etiologies -including traumatic brain injury, anoxic brain injury after cardiac arrest, and vascular injury -have been studied in the context of advanced MRI for neuroprognostication 10,29,[63][64][65][66][67][68][69][70] . In contrast, while brain network dysfunction has been observed in other etiologies of disordered consciousness -such as toxic-metabolic encephalopathy 78 -advanced MRI has not yet been shown to have prognostic value in these conditions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, sMRI has demonstrated the usefulness of white matter fractional anisotropy (FA) [4] and gray matter morphometry [5] to predict neurological outcome after CA. In addition, fMRI studies have identified putative signatures of consciousness by using either static or dynamic resting-state connectivity [6][7][8][9]. Thereby, recent fMRI studies in patients in anoxoischemic coma have shed light on the role of frontal (mesial prefrontal cortex [mPFC]) and posterior parietal (precuneus [PreCun] and posterior cingulate cortex [PCC]) cortices as critical hubs within a putative brain mesocircuit underpinning consciousness emergence and maintain [10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, resting-state functional magnetic resonance imaging (rs-fMRI) studies have demonstrated the potential diagnostic and prognostic utility of brain network mapping in patients with a broad range of brain injuries, including traumatic brain injury (TBI) (Guo et al, 2019;Kondziella et al, 2017;Peran et al, 2020;Threlkeld et al, 2018), hypoxic-ischemic injury (HIE) from cardiac arrest (Koenig et al, 2014;Norton et al, 2012;Peran et al, 2020;Pugin et al, 2020;Sair et al, 2018), and hypoxic injury from coronavirus disease 2019 (COVID-19) (Fischer et al, 2020). In addition, rs-fMRI is now used as a pharmacodynamic biomarker in early-stage clinical trials to assess brain responses to targeted therapies aimed at promoting recovery of consciousness (Edlow et al, 2020).…”
Section: Introductionmentioning
confidence: 99%